MEASURING THE EFFICIENCY OF LOCAL GOVERNMENT AGENCIES STRUCTURE: FINDING RIGHT SIZING PATTERNS - Halilul Khairi (Universitas Padjadjaran, 2020)
The purpose of this study is to determine whether the current bureaucratic structure is efficient and is actually formed to carry out managerial functions according to the needs of the tasks and functions that are carried out. This research also aims to find out that the formulation of job descriptions in structural positions has been formulated in accordance with the standard of job description formulation. Descriptive quantitative method is used to measure the structural workload of structural work units and the qualitative method is used to determine the pattern of structural job description description in the regional apparatus. An important finding in this study is that the formulation of the job description does not meet the standard rules where the task description does not contain content, methods and results / objectives. The formulation of echelon IV job descriptions also does not reflect structural task behavior patterns that describe managerial behavior. The task formulation still uses the same or even lower pattern of task behavior than the staff behavior pattern. Another important finding is that the main managerial workload in echelon IV work units generally falls into the very low workload category. So that, it can be concluded that the organizational structure at echelon IV level is less efficient because it carries out tasks whose job behavior patterns can be carried out by staff.